The Age Peculiarities of 10 to 12 Year-Old School-children - B. B. Badmayeva (Obrazovanie i Nauka, 2015)
The paper considers the problem of children’s development transformation from the standpoints of different authors. The changes in the age borders and childhood structure along with their causes are demonstrated. The childhood crisis is described, its place in the child’s development process identified. The author emphasizes the visible discord between the worlds of adults and children: being less involved in upbringing process nowadays, adults appear to be less exact in their attitude to children; their demands lack clearness and specificity. Both teachers and adults demonstrate helplessness and aloofness, which reflects in children’s consciousness and their attitude to adults, and results in the lost sense of responsibility, infantilism, egoism and moral emptiness of growing generation. The author carried out the comparative analysis of age peculiarities of middle class schoolchildren from comprehensive school. Three development stages were singled out for 10 to 12 year-olds: local caprices, rights understanding, and affirmative functional stage. The personality formation trends concerning the modern day school children are outlined, the external and internal factors determining this formation enumerated. The following influencing phenomena are mentioned, in particular: the essential socio-economic changes, fast spreading of mass-media and computer technologies, low level of parental motivation, replacement of the value-normative system (social anomie) etc. The necessity of creating socio-pedagogic conditions relating to the age peculiarities of modern school children is substantiated.